Antibacterial Activity and Mechanism of Action of Methanol Extract from Kasturi Mango Fruit (Mangifera casturi) on Caries-Causing Bacterium Streptococcus mutans - Usep Suhendar; Muhammad Fathurrahman; Sogandi Sogandi (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2019)
One of the problems frequently found in the oral cavity is dental caries caused by Streptococcus mutans. Thus far, dental caries is treated using antibiotics. However, the bacterium is known to be resistant to many antibiotics; hence, another alternative is needed. An alternative option is found in the Kasturi mango (Mangifera casturi). This study aims to identify the bioactive compounds of Kasturi mango and find out the mechanism of its action in inhibiting the growth of Streptococcus mutans. Kasturi mangoes were macerated using 96% methanol, then the phytochemical compounds were identified qualitatively. Antibacterial activity testing was carried out using the agar diffusion method, and bioactive compounds were identified using GCMS. The results showed that the methanol extract of Kasturi mango contains alkaloids, flavonoids, phenolics, terpenoids, and saponins. In 1 gr/mL of the methanol extract of Kasturi mango fruit has an inhibitory activity against the growth of Streptococcus mutans with a zone of inhibition of ± 10 mm and MIC (minimum inhibitory concentration) value of 25% extract. The inhibitory action is suspected to be through a mechanism where holes in the bacterial cell membrane are made. This can be seen from the results of SEM (scanning electron microscope) images showing that cell leakage or lysis has occurred. This research also, for the first time, revealed the types of bioactive compounds from the methanol extracts of Kasturi mango (Mangifera casturi) consisting of 18 compounds with the most abundance is 5-Hydroxymethylfurfural compounds, Octadecenoic acid, n-Hexadecanoic acid, Phenyl 4-methyl-1-piperidine carboxylate, and Methyl linolenate.